Truth or hair : a school story - Selfors, Suzanne (New York : Little, Brown and Company, 2016)
Fated to be the next Rapunzel, Holly O'Hair has long hair while her twin sister Poppy wears hers short, but when Holly's hair begins getting shorter as Poppy's grows longer, the sisters may have to reveal a secret about their fairytale destinies.
Keywords: Fairy tales -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Hair -- Fiction; Twins -- Fiction; Sisters -- Fiction; Boarding schools -- Fiction; Characters and characteristics in literature -- Juvenile fiction; Magic -- Juvenile fiction; Hair -- Juvenile fiction; Twins -- Juvenile fiction; Sisters -- Juvenile fiction; Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction